The Structures, Functions, and Roles of Class III HDACs (Sirtuins) in Neuropsychiatric Diseases - Robin E. Bonomi; William Riordan; Juri G. Gelovani (Cells, 2024)
Over the past two decades, epigenetic regulation has become a rapidly growing and influential field in biology and medicine. One key mechanism involves the acetylation and deacetylation of lysine residues on histone core proteins and other critical proteins that regulate gene expression and cellular signaling. Although histone deacetylases (HDACs) have received significant attention, the roles of individual HDAC isoforms in the pathogenesis of psychiatric diseases still require further research. This is particularly true with regard to the sirtuins, class III HDACs. Sirtuins have unique functional activity and significant roles in normal neurophysiology, as well as in the mechanisms of addiction, mood disorders, and other neuropsychiatric abnormalities. This review aims to elucidate the differences in catalytic structure and function of the seven sirtuins as they relate to psychiatry.